Catalytic Graphitization of Biomass as a Potential Method Produce Graphite In The Future : A Review - Isnanda Nuriskasari; Anne Zulfia Syahrial; Johny Wahyuadi M Soedarsono (Recent in Engineering Science and Technology, 2023)
The traditional graphitization process involves the use of non-renewable carbon sources and high temperatures, which are time-consuming and expensive. Biomass has been proposed as an alternative renewable source of carbon, which can be graphitized at lower temperatures using transition metal catalysts. The article highlights successful research on graphitization of various biomass carbon sources, such as coconut coir, whey protein, pine wood sawdust, mangosteen peel, miscanthus grass, and palm kernel shell waste, using metals as a catalyst. The graphitization process using catalysts derived from transition metals has been shown to reduce the graphitization temperature, shorten the graphitization time and improve the physicochemical properties of the resulting graphite material.